2008
DOI: 10.1029/2007jc004100
|View full text |Cite
|
Sign up to set email alerts
|

Bulge Formation of a Buoyant River Outflow

Abstract: [1] Observations taken during the Lagrangian Transport and Transformation Experiment (LaTTE) in 2005 indicated that the Hudson's river outflow formed a bulge of recirculating fluid that limits the volume of fresh water that is advected away in a coastal current. Focusing on an event that began with downwelling winds we made estimates of the freshwater flux in the coastal current and the fresh water inventory of the bulge. The coastal current was characterized by a surface advected plume in thermal wind balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 27 publications
4
84
0
Order By: Relevance
“…7). This is in agreement with observations of the Hudson plume, which demonstrate g 2 ; (0.4-0.5) for intermediate Rossby number outflows (Chant et al 2008). However, depending on the estuary configuration, more freshwater might be expected to flow downshelf.…”
Section: Discussionsupporting
confidence: 81%
“…7). This is in agreement with observations of the Hudson plume, which demonstrate g 2 ; (0.4-0.5) for intermediate Rossby number outflows (Chant et al 2008). However, depending on the estuary configuration, more freshwater might be expected to flow downshelf.…”
Section: Discussionsupporting
confidence: 81%
“…Under the influence of the Coriolis effect, the formation of anticyclonic bulges of circulating freshwater near the river mouth when the water exits the estuary has been widely described in the literature (e.g. Chao and Boitcourt, 1986;Chant et al, 2009) and observed in our study area by a local video camera system installed close to the Adour mouth (Dailloux, 2008;Morichon, 2008). Under light wind condition, Dailloux (2008) reported the development of this fresh and turbid bulge toward the west, north-west with its southern part impacting the southern beaches close to the estuary mouth.…”
mentioning
confidence: 99%
“…Late spring/early summer shelfwide freshening was also observed in glider data from previous years (Castelao et al, 2008a;Chant et al, 2008) …”
mentioning
confidence: 71%